Twenty years of digital audio watermarking—a comprehensive review - Hua, Guang (2016)
Digital audio watermarking is an important technique to secure and authenticate audio media. This paper provides a comprehensive review of the twenty years’ research and development works for digital audio watermarking, based on an exhaustive literature survey and careful selections of representative solutions. We generally classify the existing designs into time domain and transform domain methods, and relate all the reviewed works using two generic watermark embedding equations in the two domains. The most important designing criteria, i.e., imperceptibility and robustness, are thoroughly reviewed. For imperceptibility, the existing measurement and control approaches are classified into heuristic and analytical types, followed by intensive analysis and discussions. Then, we investigate the robustness of the existing solutions against a wide range of critical attacks categorized into basic, desynchronization, and replacement attacks, respectively. This reveals current challenges in developing a global solution robust against all the attacks considered in this paper. Some remaining problems as well as research potentials for better system designs are also discussed. In addition, audio watermarking applications in terms of US patents and commercialized solutions are reviewed. This paper serves as a comprehensive tutorial for interested readers to gain a historical, technical, and also commercial view of digital audio watermarking.